A novel current-limiting circuit based on resistive-type SFCL for fault in DC power system. (September 2018) - Shu, Ji; Wang, Shunliang; Liu, Tianqi; Jiao, Ning; Wang, Yanbo
Abstract: Reliability and security are essential concerns in DC power system. However, due to the limited capacity of DC circuit breaker (DCCB), the rapidly growing fault current cannot be reliably interrupted. Thus the reliability of the DC power system cannot be guaranteed. In this paper, a novel current-limiting circuit based on resistive-type superconducting fault current limiter (R-SFCL) is proposed to restrain fault current. The operation procedure of the proposed current-limiting circuit is presented in detail. Then, a detailed mathematical model of opening process is established to analyse parameter design. Finally, the simulation results verify the effectiveness of this circuit. Compared with the traditional current limiting solutions, the proposal can effectively limit the fault current to achieve a more reliable breaking serious fault, and the reliability of DC system can be improved. Furthermore, overvoltage on DCCB is also prevented so that the arrester can be cancelled. Graphical abstract: Highlights: Fault current limited without using a big inductor. Fault current can be reliably interrupted even if serious fault occurs. Overvoltage on DCCB is prevented during the opening process. Fault isolation time decreased.